Sphingosine-1-phosphate signaling in Leishmania donovani infection in macrophages. - Mohd Arish; Atahar Husein; Rahat Ali; Shams Tabrez; Farha Naz; Mohammad Zulfazal Ahmad; Abdur Rub (Public Library of Science (PLoS), 2018)
BACKGROUND:Sphingosine-1-phosphate (S1P) is a crucial regulator of a wide array of cellular processes, such as apoptosis, cell proliferation, migration, and differentiation, but its role in Leishmania donovani infection is unknown. METHODOLOGY/ PRINCIPAL FINDINGS:In the present study, we observed that L. donovani infection in THP-1 derived macrophages (TDM) leads to decrease in the expression of S1pr2 and S1pr3 at mRNA level. We further observed that Leishmania infection inhibits the phosphorylation of sphingosine kinase 1 (sphK1) in a time-dependent manner. Exogenous S1P supplementation decreases L. donovani induced ERK1/2 phosphorylation and increases p38 phosphorylation in TDM, resulting in a decrease in the intracellular parasite burden in a dose-dependent manner. On the other hand, sphK inhibition by DMS increases ERK1/2 phosphorylation leading to increased IL-10 and parasite load. To gain further insight, cytokines expression were checked in S1P supplemented TDM and we observed increase in IL-12, while decrease IL-10 expression at mRNA and protein levels. In addition, treatment of antagonist of S1PR2 and S1PR3 such as JTE-013 and CAY10444 respectively enhanced Leishmania-induced ERK1/2 phosphorylation and parasite load. CONCLUSIONS:Our overall study not only reports the significant role of S1P signaling during L. donovani infection but also provides a novel platform for the development of new drugs against Leishmaniasis.